Pengaruh Model Pembelajaran Novick Terhadap Kemampuan Pemahaman Konsep Matematika Siswa Kelas XI MIPA SMAN 1 Campalagian - Rahma, Rahma; Nur Fahri Tadjuddin; Sartika Arifin (Pendidikan Matematika FKIP Universitas Mataram, 2024)
The purpose of this study is to determine whether the mathematical conceptual understanding ability of 11th grade MIPA students at SMAN 1 Camapalagian, taught using the Novick learning model, is higher compared to those taught using the direct learning model. This research is a quasi experiment with a nonequivalent control grup design. The study was conducted at SMAN 1 Campalagian during the academic year 2023-2024, with class XI MIPA 2 designated as the experimental group and class XI MIPA 1 as the control group. Data collection techniques involved administering tests on mathematical conceptual understanding ability and observation sheets. Data analysis techniques included descriptive and inferential analysis using SPSS 23. Descriptive statistical analysis showed that the average pretest score for the experimental group was 15,84 while for the control group, it was 15,17. The average posttest score for the experimental class was 78,72, while the average posttest score for the control class was 65,09. Hypothesis testing using an independent sample t-test yielded a significance value of 0,00000045 < 0,05 , therefore, the null hypothesis (H0) was rejected, and the alternative hypothesis (H1) was accepted, indicating that the mathematical conceptual understanding ability of 11th grade MIPA students at SMAN 1 Campalagian, taught using the Novick learning model, is higher compared to those taught using the direct learning model.